Is trimethoprim/sulfamethoxazole-associated increase in serum creatinine a pseudo-elevation or true nephrotoxicity?. Issue 8 (August 2021) - Urakami, Toshiharu; Hamada, Yohei; Oka, Yusuke; Kannae, Mikinori; Okinaka, Tomohide; Sanada, Ayaka; Shimanoe, Chisato; Aoki, Yosuke
Abstract: Introduction: The aim of this study was to determine the rates of trimethoprim/sulfamethoxazole (TMP/SMX)-associated pseudo-elevation and true nephrotoxicity by comparison of creatinine-estimated and cystatin C-estimated GFRs (glomerular filtration rates) before and after TMP/SMX administrations. Methods: Patients in whom serum creatinine and cystatin C were simultaneously measured are the cohort of this study. A decreasing of creatinine-estimated GFR posterior to TMP/SMX by ≥ 20% and a decreasing of cystatine C-estimated GFR posterior to TMP/SMX by ≥ 20% were defined as true nephrotoxicity. A decreasing of creatinine-estimated GFR posterior to TMP/SMX by ≥ 20% and a decreasing of cystatine C-estimated GFR posterior to TMP/SMX by < 20% were defined as pseudo-elevation. Results: A total of 66 patients were enrolled. Within the 19 patients in whom serum creatinine and cystatin C were measured simultaneously both before and after TMP/SMX administrations, 10 patients (52.6%) had nephrotoxicity. Fewer random error and systematic bias between creatinine- and cystatine C-estimated GFR were observed after TMP/SMX than before TMP/SMX by Bland-Altman analysis. Conclusions: Using cystatin C, we reveled TMP/SMX-associated nephrotoxicity is not uncommon. We should equally pay attention to TMP/SMX-associated nephrotoxicity and pseudo-elevation. In spite of pseudo-elevation, creatinine-estimated GFR after receiving TMP/SMX is ironically reliable as surrogate maker for renal clearance.